(untitled) (World Economics and Finance Bulletin, 2025)
This study aims to identify the level of sustainability accounting within the framework of governance measurement and the prevailing financial reports of commercial banks listed in the Iraq Stock Exchange. This is done by analyzing the financial reports of a sample of banks listed in the Iraq Stock Exchange to measure their level of governance compliance in their financial reports and its reflection in those reports. In addition, the study analyzes the opinions of stakeholders and beneficiaries of the reports of these commercial banks and examines data collected through a questionnaire prepared for this purpose and validated by a group of specialists. This is to understand the measurement of governance and financial reports and their relationship with sustainability accounting within the accounting system of banks, as well as to identify the effect of governance and disclosure on sustainability accounting. Ultimately, this impacts the financial reports and the information contained therein, which may be used in decision-making by beneficiaries based on information that may not accurately represent economic activities. Moreover, the competition among these banks to increase their market shares reflects their banking and investment activity, which affects the measurement of their financial reports. The influence of governance on the process of sustainable measurement is also evident through other factors, which may direct the type of decision made based on an environment oriented within a business framework